Patient education on nasal spray technique for allergic rhinitis - Nasir, Fauziah B.; Mann, Balwinder S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Allergic rhinitis (AR) is a common condition worldwide. Intranasal corticosteroid spray (INCS) is the mainstream and effective first line monotherapy treatment of AR. However, the efficacy of INCS may be dependent on factors such as the patient’s compliance and delivery technique of the nasal spray. The correct delivery technique of INCS depends on the adequacy of patient education. Hence, our study was conducted to assess the benefit of the different methods of patient education and the best method of patient education on INCS usage technique. Objectives of the study were to determine if proper education in the usage of ICNS affected the treatment of AR and to determine the best teaching method of nasal spray technique using both subjective and objective methods of assessment. Methods: This is a prospective study that was performed over 2 years duration from the year 2017 until 2019. A total of 96 patients were recruited based on our inclusion and exclusion criteria. The effectiveness of the different methods of teaching were determined both subjectively by total nasal symptom score (TNSS) and objectively using Rhinomanometry test. The teachings method became increasingly more comprehensive as compared to the previous visit. Assessment was done every six weeklies for 4 times after each teaching methods of nasal spray usage on each visit. All Rhinometry test and patients follow up of was done by the same surgeon. Results: There was statistically significant improvement (p<0.05) in patients symptoms based on the nasal resistance and TNSS with more comprehensive method of teaching nasal spray. Conclusions: Our study showed the importance of educating patient regarding the use of INCS. Both objective and subjective assessment of improvement after each method of patient education showed statistically significant outcome.